THE FINANCIAL SYSTEM OF THE SOUTH AFRICA COUNTRIES - E. S. Romanchuk (Финансы: теория и практика)
The development of regional integration in Southern Africa leads to the need to harmonize the financial system and financial policy of the States-members of SADC. In this context the analysis of the Southern African States financial systems becomes relevant to identify their similarities and differences. On the basis of this analysis the following conclusions were made.The indicators of financial markets development remain relatively low. Markets are shallow, lack of liquidity, fragmentation, and exposure to high volatility due to macroeconomic or political instability in the international markets. However, it is worth noting that States are attempting to market expansion and filling their liquidity, including through the issuance of sovereign Eurobonds.The levels of financial markets development in the region vary because of different financial systems in these countries and different financial instruments.The banking sector dominates in all financial systems.Large proportion of the population has no access to the financial market in the region, resulting in parallel withexisting formal informal financial market not only in economically weak States, but in relatively stable. Moreover, SADC has turned into a jurisdiction with a low level of risk for organized crime and money laundering. The development of microfinance, designed inter alia to derive the finance in the formal sector of the economy, however, masks the structural and qualitative changes.Thus, member States of SADC are not yet ready to harmonize and unify the financial system and to conduct a unified fiscal policy.